2012
DOI: 10.1103/physreva.86.026701
|View full text |Cite
|
Sign up to set email alerts
|

Comment on “Experimental and theoretical study of the triple-differential cross section for electron-impact ionization of thymine molecules”

Abstract: In their recent paper, Bellm et al. [Phys. Rev. A 85, 022710 (2012)] performed (e,2e) experiments on thymine at an incident energy of 250 eV. They wrote in the conclusion that a model based on the first Born approximation using the completely neglected differential overlap description is in very good agreement with the experimental data. On the contrary, we argue that this model fails to describe experiments on water performed at the same incident energy and is unable to explain any shift of the binary or reco… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2013
2013
2019
2019

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 30 publications
1
2
0
Order By: Relevance
“…We notice a relative good agreement with the relative experimental data of Bellm et al [4]. A complete study of the single ionization of thymine can be found in [86][87][88].…”
Section: Theorysupporting
confidence: 90%
“…We notice a relative good agreement with the relative experimental data of Bellm et al [4]. A complete study of the single ionization of thymine can be found in [86][87][88].…”
Section: Theorysupporting
confidence: 90%
“…In the past recent years, extensive research has been conducted to measure and calculate the triple differential cross sections (TDCSs) for molecules of biological interest [6][7][8][9][10][11][12][13][14][15][16].…”
Section: Introductionmentioning
confidence: 99%
“…One of these methods is the multi-center distorted wave model where non-diagonal terms in the potential matrix are ignored to make the calculations possible [27][28][29][30]. Another approximation is to calculate the TDCS as a weighted sum of atomic TDCSs corresponding to the atoms of the molecule, in the completely neglected differential overlap description, which fails in reproducing the experimental TDCS for many molecules [7,31]. To our knowledge, the methodology that we propose is the only one that allows the calculation of the TDCSs for complex targets without having to make such drastic approximations.…”
Section: Introductionmentioning
confidence: 99%